Determinants of green innovations: Firm-level evidence - Iulia Siedschlag; Stefano Meneto; Manuel Tong Koecklin (The Economic and Social Research Institute (ESRI), 2019)
This paper examines determinants of firms' innovations with environmental benefits. Using micro-data from Ireland, we identify and quantify the impact of environmental regulations, innovation-inputs, firm-specific characteristics, spillovers from other green innovators, public funding and innovation co-operations on the propensity of firms to introduce innovations with environmental benefits. In addition, the analysis distinguishes innovations with environmental benefits within the enterprise and innovations with environmental benefits for the final consumer as well as different innovations by type of environmental impact within these two broad categories of green innovations. The results indicate that environmental regulations, in-house R&D and acquisition of capital assets are crucially important as drivers of green innovations.
Keywords: D22; F23; L51; Q55; 330; innovations with environmental benefits; firm behaviour; environmental regulations; multinational activity